Improving Student's Mathematics Problem Solving Ability in the Trial of the Kaulinan Barudak Application as a Mathematics Learning Media - Irawan, Ari; Rahayu, Wanti; Nuzulah, Rahnita (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
The problem-solving ability of students is still very low, so there is a need for media that can facilitate these abilities. Android-based learning media that is integrated with local wisdom of traditional games and mathematics in providing a new color for learning activities. This research aims to test whether the Kaulinan Barudak ethnomathematics android application that the researcher is making can improve students' problem-solving abilities. In addition, this research activity seeks to see how the user responds to the Kaulinan Barudak android application. The method used in this research is Research and Development (RnD) with the Borg and Gall model. There are 10 stages in this model, namely potential, data collection, product design, design validation, revision, product trial, revision, user experiment, revision, and mass production. Meanwhile, this research is already at the user trial stage. The experiment was conducted on 30 students of Junior High School/MTs Al Hidayah class VIII. Next, look to see if there are differences before and after treatment with applications using pre-test and post-test. The results of this research are (1) This research has provided an overview of the user's response to the Kaulinan Barudak ethnomathematics application which is not valid and feasible to be used as a medium for learning mathematics for seventh-grade students of junior high school; and (2) This research proves that with the use of the Kaulinan Barudak application, the student's understanding ability increases, this can be seen from the average pre-test and post-test and the results of the t-test that have been carried out.